PENGARUH PEMBERIAN KONSUMSI TABLET TAMBAH DARAH (Fe) DAN BUAH KURMA TERHADAP PENINGKATAN HB IBU HAMIL ANEMIA DIWILAYAH KERJA PUSKESMAS PANAAN - Nurislamiyah, Nurislamiyah; Handayani, Lisda; Noval, Noval (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Anemia in pregnancy is dangerous for the mother or fetus. The consequences that can occur if pregnant women suffer from anemia, namely miscarriage, premature birth, KPD can occur during childbirth with his, old partus. postpartum hemorrhage, puerperal infection, as well as decreased milk production. The purpose of the study was to determine the effect of giving blood-added tablets (Fe) and dates in increasing Hb levels in anemic pregnant women. The research method uses the quasy experimental method with the Pretest-Posttest Control Group Design design. The design of this study was a group divided into 3, intervention group I (Fe tablets and dates), intervention group II (dates) and control group (Fe tablets). Data were analyzed using the Wilcoxon test. The results of the study of 15 respondents of anemic pregnant women after the intervention, all respondents experienced an increase in Hb. The highest increase in Hb was in the intervention group I average value of 1.44 mg / dl and from the results of the Wilcoxon test obtained a p-value of 0.043, intervention group II an average increase in Hb 0.62 mg / dl and obtained a p-value of 0.042, intervention group III an average increase in Hb of 0.46 mg / dl with a p-value of 0.041.